Evaluation of South African common bermudagrass germplasm for shade tolerance. Issue 1 (27th April 2022) - Carbajal Melgar, Esdras M.; Miller, Grady L.; Dunne, Jeffrey C.; Schwartz, Brian M.; Milla‐Lewis, Susana R.
Abstract: Common bermudagrass ( Cynodon dactylon L. Pers.) is a widely grown warm‐season turfgrass species characterized by a dense, deep‐rooted canopy and high levels of traffic tolerance. However, most cultivars have poor shade tolerance, which limits the use of these grasses in partly‐shaded areas. The identification of new sources of genetic resistance to shade will expand the germplasm pool available to breeders for developing improved bermudagrass cultivars. In this study, 24 common bermudagrass accessions recently introduced from South Africa were evaluated for their ability to persist under shade. Entries were established in a randomized complete block design with three replications at the Lake Wheeler Turfgrass Field Lab (Raleigh, NC) in the spring of 2019. Following full green‐up in summer 2020, entries were evaluated for performance under full sun, and then a 63% shade cloth was installed over the plots. Traits evaluated under shade included: turfgrass quality, turfgrass density, genetic color, ground coverage, turfgrass regrowth and the normalized difference vegetation index (NDVI). A turfgrass performance index (TPI) was calculated to identify the top performers across all traits. Under full sun, seven accessions had comparable performance with 'Celebration' and 'TifTuf' across traits. Under shade, 'Stil03', 'Q 47620', 'TifGrand', 'WIN10F', Celebration, and TifTuf exhibited the highest TPI. Accessions with superior shade tolerance identified in this study represent novel germplasm that can be used in future breeding efforts to improve shade tolerance in bermudagrass. Core Ideas: We evaluated 24 newly introduced common bermudagrass accessions for shade tolerance. Normalized difference vegetation index, percentage of green cover, and percentage of regrowth were evaluated under 63% shade. A turfgrass performance index was calculated to identify the top performers across traits. Stil03, WIN 10F, and Q 47620 have high levels of shade tolerance. These accessions represent new sources of genetic resistance to shade for use in breeding.